Construction Technology. 3, The technology of refurbishment and maintenance - Riley, Mike, 1964-; Cotgrave, Alison (2011)
Designed in a structured, directed format to help develop understanding, rather than just providing a simple source of information, this textbook offers comprehensive coverage of the refurbishment and maintenance of existing buildings, with a focus on the environmental impact of refurbishment rather than new build in the context of sustainability.
Previous edition: 2005.
Includes index.
Keywords: Buildings -- Repair and reconstruction -- Great Britain; Buildings -- Maintenance -- Great Britain; House and Home